Pharmacokinetics and plasma concentrations of acetylsalicylic acid after intravenous, rectal, and intragastric administration to horses - Broome, Ted A. (2003)
Six healthy adult horses (5 mares and 1 stallion) were given a single dose of acetylsalicylic acid (ASA), 20 mg/kg of body weight, by intravenous (IV), rectal, and intragastric (IG) routes. Serial blood samples were collected via jugular venipuncture over a 36-h period, and plasma ASA and salicylic acid (SA) concentrations were determined by high-performance liquid chromatography. After IV administration, the mean elimination rate constant of ASA (± the standard error of the mean) was 1.32 ± 0.09 h(−)l, the mean elimination half-life was 0.53 ± 0.04 h, the area under the plasma concentration-versus-time curve (AUC) was 2555 ± 98 μg · min/mL, the plasma clearance was 472 ± 18.9 mL/h/kg, and the volume of distribution at steady state was 0.22 ± 0.01 L/kg. After rectal administration, the plasma concentration of ASA peaked at 5.05 ± 0.80 μg/mL at 0.33 h, then decreased to undetectable levels by 4 h; the plasma concentration of SA peaked at 17.39 ± 5.46 μg/mL at 2 h, then decreased to 1.92 ± 0.25 μg/mL by 36 h. After rectal administration, the AUC for ASA was 439.4 ± 94.55 μg · min/mL and the bioavailability was 0.17 ± 0.037. After IG administration, the plasma concentration of ASA peaked at 1.26 ± 0.10 μg/mL at 0.67 h, then declined to 0.37 ± 0.37 μg/mL by 36 h; the plasma concentration of SA peaked at 23.90 ± 4.94 μg/mL at 4 h and decreased to 0.85 ± 0.31 μg/mL by 36 h. After IG administration, the AUC for ASA was 146.70 ± 24.90 μg · min/mL and the bioavailability was 0.059 ± 0.013. Administration of a single rectal dose of ASA of 20 mg/kg to horses results in higher peak plasma ASA concentrations and greater bioavailability than the same dose given IG. Plasma ASA concentrations after rectal administration should be sufficient to inhibit platelet thromboxane production, and doses lower than those suggested for IG administration may be adequate.